Green Synthesis of Silver Nanoparticles Using Apple Extract and Its Antibacterial Properties - Ali, Z.A.; Yahya, R.; Sekaran, S.D.; Puteh, R. (Hindawi Publishing Corporation, 2016)
Silver nanoparticles (AgNPs) were synthesized using apple extract as a reducing agent and aqueous silver nitrate as the precursor. The AgNPs formation was observed as a color change of the mixture from colorless to dark-brownish. The X-ray diffraction pattern confirmed the presence of only Ag crystallites, and the dynamic light scattering estimates the average sizes of the AgNPs to be 30.25 ± 5.26 nm. Furthermore, Fourier Transform Infrared as well as UV-vis spectroscopy identifies ethylene groups as the reducing agent and capping agent for the formation of the AgNPs. This green synthesis provides an economic, eco-friendly, and clean synthesis route to AgNPs. AgNPs in suspension showed activity against Gram-negative and Gram-positive bacteria with minimum bactericidal concentrations (MBCs) to be in the range from 125 μg/mL to 1000 μg/mL.